Ethical Issues in Care and Treatment of Neuronal Ceroid Lipofuscinoses (NCL)–A Personal View - Kohlschütter, Alfried (Frontiers in Neurology, 2021)
The management of Neuronal Ceroid Lipofuscinoses (NCL), a group of genetic neurodegenerative disorders mainly affecting brain and retinas, raises difficult questions for physicians and other professionals in research, pharmaceutical industry, and public health. Ethical problems in medicine cannot be solved by rational deliberation or by following formal rules. Two topics of ethical issues in the field of NCL are presented here. One group relates to the care of individual patients and centers on a life with dementia at a young age. Advanced care planning for the end of life and the use of life-prolonging measures require challenging assumptions in the best interest of a patient. A second group of questions relates to new treatments. Impressive novel putative causal therapies, such as enzyme replacement for CLN2 disease, may be only disease-modifying and carry the risk of changing a deadly disease of short duration into one with prolonged survival and poor quality of life. The wish for better therapeutic interventions in life-limiting diseases has to take such risks, but more experience is needed before definite conclusions can be drawn. The appropriateness of presymptomatic screening for a severe disease, e.g., must be carefully evaluated to avoid the disastrous experience made with the rash start of newborn screening for Krabbe disease. The ethical issues described and commented in the article reflect the personal experience of a pediatrician who has studied clinical and research questions in NCL for four decades. They should alert various professionals to the necessity of taking their own decisions in situations that are caused by rare progressive brain diseases of young persons, as typified by the NCL.